Estimativa da economia com geração distribuída fotovoltaica dos consumidores residenciais no estado do Paraná - Leal, Felipe Serenato (2021)
Distributed generation is proving to be a highly viable alternative and still has great potential to be explored. An in-depth survey of this potential, combined with an analysis evaluating this impact from an economic point of view, can serve as a guide for the implementation of public policies, or even for the performance of companies in this segment. This work evaluated the consumption history and location of more than 3 million residential consumers in Paraná for dimensioning the photovoltaic systems and calculating the energy bill of these units. For this, data cleaning techniques were used and later routines were implemented in the python programming language. The residential units in Paraná present a potential savings of 72%, totaling an annual savings of R$2.4 billion.